PENGARUH NON PERFORMING LOAN (NPL), CAPITAL ADEQUACY RATIO (CAR) DAN INFLASI TERHADAP PENYALURAN KREDIT USAHA RAKYAT (KUR) : THE INFLUENCE OF NON PERFORMING LOAN (NPL), CAPITAL ADEQUACY RATIO (CAR) AND INFLATION ON DISTRIBUTION OF BUSINESS CREDIT - Shella Yoseva Simangunsong; Nurhadi Nurhadi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study intends to examine the effects of macroeconomic factors like inflation on KUR distribution for the years 2018 through 2021, as well as the effects of bank financial parameters including the capital adequacy ratio (CAR) and non-performing loans (NPL). In this study, the population consists of 40 banks, and 23 banks were selected using a purposive selection technique. Utilize multiple linear regression and SPSS 24 to analyze the research's data. According to the analysis's findings, the simultaneous effects of non-performing loans (NPL), capital adequacy ratio (CAR), and inflation have a substantial impact on the distribution of KUR. The study's findings indicate that while partly non-performing loans (NPLs) and inflation had no discernible impact on the distribution of KUR in banks that acted as conduits for KUR during the 2018–2021 timeframe, the Capital Adequacy Ratio (CAR) had a positive and substantial impact.